Collaboration over competition? Regulatory reform and inter-organisational relations in the NHS amidst the COVID-19 pandemic: a qualitative study - Justin Avery Aunger; Ross Millar; Anne Marie Rafferty; Russell Mannion (BMC, 2022)
Abstract Background In 2021, during the COVID-19 pandemic, England's Department of Health and Social Care (DHSC) released a White Paper outlining proposed legislative reform of the National Health Service (NHS). Key to the proposals is the shift from relationships between providers based on competition, to cooperation, as the central driver of improved performance and quality. Against this background we explore potential regulatory barriers and enablers to collaboration identified by key NHS stakeholders and assess whether the proposed policy changes are likely to deliver the desired improvement in collaborative relationships, in the context of challenges experienced during the COVID-19 pandemic. Methods We conducted 32 semi-structured interviews with 30 key stakeholders, taking place during the COVID-19 pandemic from Jan 2020 to May 2021. Participants were selected for their expertise regarding collaboration and were recruited purposively. Interviews were conducted online with the use of video conferencing software. The interviews were thematically analysed to identify themes. Proposals contained in the DHSC White Paper helped to structure the thematic analysis, interpretation, and reporting of the results. Results Requirements to compete to provide services, regulatory ability to block collaborative arrangements, lack of collaboration between providers and Clinical Commissioning Groups, and current lack of data sharing were found to hamper collaborative efforts. These issues often negatively affected collaborative relations by increasing bureaucracy and prompted leaders to attempt to avoid future collaborations. Other barriers included opaque accountability arrangements, and erosion of trust in regulators. The COVID-19 pandemic was found to foster collaboration between organisations, but some changes mandated by the new legislation may stifle further collaboration. Conclusions Many of the proposed legislative changes in the White Paper would help to remove existing barriers to service integration and collaboration identified by stakeholders. However, the proposed shift in the concentration of power from NHS England to the DHSC may exacerbate historically low levels of trust between providers and regulators. Many of the proposed changes fail to address endemic NHS policy issues such as chronic understaffing. Further dialogue is needed at all levels of the health and social care system to ensure future legislative changes meet the needs of all stakeholders.